If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + -9 = 10p + -49 Reorder the terms: -9 + 2p = 10p + -49 Reorder the terms: -9 + 2p = -49 + 10p Solving -9 + 2p = -49 + 10p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-10p' to each side of the equation. -9 + 2p + -10p = -49 + 10p + -10p Combine like terms: 2p + -10p = -8p -9 + -8p = -49 + 10p + -10p Combine like terms: 10p + -10p = 0 -9 + -8p = -49 + 0 -9 + -8p = -49 Add '9' to each side of the equation. -9 + 9 + -8p = -49 + 9 Combine like terms: -9 + 9 = 0 0 + -8p = -49 + 9 -8p = -49 + 9 Combine like terms: -49 + 9 = -40 -8p = -40 Divide each side by '-8'. p = 5 Simplifying p = 5
| 25+(-10)= | | 6(z+1)=5z | | -9(z+8)=-9z-7 | | 13x+16=42 | | 2a+b=0.125 | | 18x^3/2x | | 6x/5*3y/7 | | 21x+16-8x=42 | | 7/8x3/4= | | 8z+1-z=6+6z+6 | | 4*x=x | | Y=x^3+c^2-12x | | hbt=2(3.14) | | 0.75x=92 | | 3y=19x+86 | | (3y^3/4a^5y)*(10a^3/y) | | (n+6)(n-6)=5n | | 7+6x=5+3x | | -6=-5x+x^2 | | 11(v+4)-3v=4(2v+3)-17 | | 27d^6+8g^12=0 | | 3+2w=19 | | (x)=-2x^2+7x-4 | | 2lnx+4=5+lnx | | wx^2-w^2x^2=0 | | F(x)=5x^2+10x+12 | | 6t+8=26-3t | | 6y-1=8y-3y | | x/2=3-x/4 | | 8x^3-12x^2-10x+15= | | (x-1)/7-(x-3)/2=1 | | X=4x^2-9x+2 |